The role of neuroinflammation in cerebral amyloid angiopathy - Hilde van den Brink; Sabine Voigt; Mariel Kozberg; Ellis S. van Etten (EBioMedicine)
Summary: Cerebral amyloid angiopathy (CAA) is a cerebrovascular disease characterized by vascular amyloid-β (Aβ) deposition. CAA is often seen in the brains of elderly individuals and in a majority of patients with Alzheimer's disease. The molecular pathways triggered by vascular Aβ, causing vessel wall breakdown and ultimately leading to intracerebral haemorrhage and cognitive decline, remain poorly understood. The occurrence of CAA-related inflammation (CAA-ri) and Amyloid-Related Imaging Abnormalities (ARIA) have sparked interest for a role of neuroinflammation in CAA pathogenesis. This review discusses prior studies of neuroinflammation in CAA and outlines potential future research directions targeting candidates such as matrix metalloproteinases, complement activation, microglial activation, reactive astrocytes and parenchymal border macrophages. Understanding the role of neuroinflammation in CAA pathogenesis could help identify new therapeutic strategies.